2020
DOI: 10.1155/2020/1083251
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Gastrointestinal Parasites of Baboons (Papio anubis) in the Shai Hill Reserve in Ghana

Abstract: Several intestinal parasites of baboons are of zoonotic importance, especially where there is considerable interaction between the baboons and humans. The identification of gastrointestinal parasite infections of baboons (Papio anubis) was undertaken at the Shai Hills Reserve Resort, Ghana. A total of 51 faecal samples were collected randomly from individual baboons (51) and examined for cysts, eggs, and larvae of parasites of medical importance, using the direct saline smear and formol-ether concentration tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…In the present study, the high infection in adult's animals than the young animals concurs with [10] who observed that adults had the highest prevalence of intestinal parasites (39%), while the juveniles (18%) had the least. There was no relationship between age and parasite abundance was observed, except for baboon where age was found to be associated with prevalence of two parasite taxa (Strongyloides sp.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the high infection in adult's animals than the young animals concurs with [10] who observed that adults had the highest prevalence of intestinal parasites (39%), while the juveniles (18%) had the least. There was no relationship between age and parasite abundance was observed, except for baboon where age was found to be associated with prevalence of two parasite taxa (Strongyloides sp.…”
Section: Discussionsupporting
confidence: 92%
“…The high prevalence of GIP of 95.38 % (227 out of 238) found from the animals in the two forests is consistence with [10] who reported a total prevalence of 92 % zoonotic Gastrointestinal Parasites in Baboons (Papio anubis) in the Shai Hill Reserve in Ghana. In their survey [11] revealed a high prevalence of GIP, where 86% (48/56) of faecal samples screened positive for parasitic infections.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…( 2019 ) and Larbi et al . ( 2020 ) have each noted whipworm infections in baboons previously, and whipworm control in people is a major ongoing effort across the world (WHO, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal parasites of various baboon species living in wild, or in conservation settings, are well documented over decades of study using necropsy and coprological surveys (Myers and Kuntz, 1965 ; Murray et al ., 2000 ; Hahn et al ., 2003 ; Hope et al , 2004 ; Fagiolini et al ., 2010 ; Mafuyai et al ., 2013 ; Ebbert et al ., 2015 ; Reichard et al ., 2017 ; Akinyi et al ., 2019 ; Eo et al ., 2019 ; Mbuthia et al ., 2021 ). The gastrointestinal parasites of olive baboons have been frequently studied in different countries, sometimes with DNA characterization of encountered parasites (Ko et al ., 2023 ), to assess their zoonotic potentials (Müller-Graf et al ., 1996 ; Munene et al ., 1998 ; Bezjian et al ., 2008 ; Ryan et al ., 2012 ; Larbi et al ., 2020 ; Tabasshum et al ., 2022 ) that might have bearing for this UK safari park setting.…”
Section: Introductionmentioning
confidence: 99%